Gold Nanoparticles Stabilized by Glycodendrimers: Synthesis and Application to the Catalytic Reduction of 4‐Nitrophenol. Issue 16 (2nd May 2014) - Gatard, Sylvain; Salmon, Lionel; Deraedt, Christophe; Ruiz, Jaime; Astruc, Didier; Bouquillon, Sandrine
Abstract: Air‐stable gold nanoparticles stabilized by glycodendrimers (AuDSNs) in water were prepared in the presence of a reducing agent, NaBH4 . A UV/Vis spectroscopy study demonstrates that no spontaneous reduction of Au 3+ ions occurs in the presence of glycodendrimers. The AuDSNs were characterized by UV/Vis spectroscopy and transmission electron microscopy (TEM). TEM images show that the AuDSNs were very small (average diameter: 2.6 nm). The catalytic activity of these AuDSNs was evaluated for the reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) by NaBH4 monitored by UV/Vis spectroscopy. Studies of the reduction reaction reveal that the rate constant depends on the concentration of 4‐NP. Abstract : Air‐stable gold nanoparticles stabilized by glycodendrimers (AuDSNs) in water were prepared in the presence of a reducing agent, NaBH4 . The AuDSNs were characterized by UV/Vis spectroscopy and transmission electron microscopy. Their catalytic activity was evaluated for the reduction of 4‐nitrophenol to 4‐aminophenol by NaBH4 .